The Rag Trade - television programme, 1963 (London, 1963)
1963 1961-70 "The Rag Trade - television programme, 1963" [BW0160], 1963, Trades Union Congress The Rag Trade was broadcast by the BBC between 1961 and 1963 and by London Weekend Television between 1977 and 1978 and set in a small clothing workshop, Fenner Fashions in London. Although run by Harold Fenner (Peter Jones) and Reg the foreman (Reg Varney), the women workers were always ready to strike, led by militant shop steward Paddy Fleming (Miriam Karlin), with the catchphrase "Everybody out!" Other cast members included Sheila Hancock (as Carole), Esma Reese Cannon (as Lily Swann), Wanda Ventham (as Shirley) and Barbara Windsor (as Judy). This photo is from the Association of Cinematograph, Television and Allied Technicians journal Film and Television Technician February 1963.